2020
DOI: 10.1177/0300060520964016
|View full text |Cite
|
Sign up to set email alerts
|

Combination effects of a fatty diet and exercise on the depressive state and cardioprotection in apolipoprotein E knockout mice with a change inRCAN1expression

Abstract: Objective Regulator of calcineurin 1 (RCAN1) controls plasticity of the nervous system and depressive conditions by regulating brain-derived neurotropic factor (BDNF) and plays a crucial role in neural and cardiac pathways. The apolipoprotein E gene ( ApoE) is a robust risk factor for progression of Alzheimer’s disease. A fatty diet is considered detrimental for metabolic disorders, such as obesity and cardiovascular diseases. Methods We examined the neuronal and cardiac protective roles of RCAN1 in ApoE−/− mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Increasing Twinkle expression in transgenic mice aims to improve mitochondrial function, preserve mtDNA integrity, and counteract the effects of mitochondrial dysfunction on aging processes, including atherosclerosis and vascular aging. Studies in Apoe−/−mice on a standard diet plan showed high damage to vascular mtDNA but not nuclear DNA with aging (Shuo et al, 2020). Similarly, atherosclerotic plaques in humans and Apoe−/−mice on a high-fat diet contain lower levels of mitochondrial complex I and complex II compared to undamaged areas of the aorta (Zhang et al, 2016).…”
Section: Vascular Mitochondrial Dysfunction During Atherogenesismentioning
confidence: 99%
“…Increasing Twinkle expression in transgenic mice aims to improve mitochondrial function, preserve mtDNA integrity, and counteract the effects of mitochondrial dysfunction on aging processes, including atherosclerosis and vascular aging. Studies in Apoe−/−mice on a standard diet plan showed high damage to vascular mtDNA but not nuclear DNA with aging (Shuo et al, 2020). Similarly, atherosclerotic plaques in humans and Apoe−/−mice on a high-fat diet contain lower levels of mitochondrial complex I and complex II compared to undamaged areas of the aorta (Zhang et al, 2016).…”
Section: Vascular Mitochondrial Dysfunction During Atherogenesismentioning
confidence: 99%
“…The open-field test was performed to assess spontaneous locomotor activity and anxiety-like behavior, as described previously (Shuo et al, 2020). Mice were placed individually in a circular open-field chamber (diameter, 80 cm; height, 50 cm).…”
Section: Open-field Testmentioning
confidence: 99%